Probing the structural basis for differential KCNQ1 modulation by KCNE1 and KCNE2 - Wang, Yuhong (The Rockefeller University Press, 2012)
KCNE1 associates with KCNQ1 to increase its current amplitude and slow the activation gating process, creating the slow delayed rectifier channel that functions as a “repolarization reserve” in human heart. The transmembrane domain (TMD) of KCNE1 plays a key role in modulating KCNQ1 pore conductance and gating kinetics, and the extracellular juxtamembrane (EJM) region plays a modulatory role by interacting with the extracellular surface of KCNQ1. KCNE2 is also expressed in human heart and can associate with KCNQ1 to suppress its current amplitude and slow the deactivation gating process. KCNE1 and KCNE2 share the transmembrane topology and a high degree of sequence homology in TMD and surrounding regions. The structural basis for their distinctly different effects on KCNQ1 is not clear. To address this question, we apply cysteine (Cys) scanning mutagenesis to TMDs and EJMs of KCNE1 and KCNE2. We analyze the patterns of functional perturbation to identify high impact positions, and probe disulfide formation between engineered Cys side chains on KCNE subunits and native Cys on KCNQ1. We also use methanethiosulfonate reagents to probe the relationship between EJMs of KCNE subunits and KCNQ1. Our data suggest that the TMDs of both KCNE subunits are at about the same location but interact differently with KCNQ1. In particular, the much closer contact of KCNE2 TMD with KCNQ1, relative to that of KCNE1, is expected to impact the allosteric modulation of KCNQ1 pore conductance and may explain their differential effects on the KCNQ1 current amplitude. KCNE1 and KCNE2 also differ in the relationship between their EJMs and KCNQ1. Although the EJM of KCNE1 makes intimate contacts with KCNQ1, there appears to be a crevice between KCNQ1 and KCNE2. This putative crevice may perturb the electrical field around the voltage-sensing domain of KCNQ1, contributing to the differential effects of KCNE2 versus KCNE1 on KCNQ1 gating kinetics.